2020
DOI: 10.20319/pijss.2020.53.881894
|View full text |Cite
|
Sign up to set email alerts
|

Peer Tutoring: Exploring the Effects on Learning Grade 9 Mathematics

Abstract: This descriptive-comparative study aimed to develop session plans with learning activities for peer tutoring on quadratic equations. It involved five classes of Grade 9 students of Bantayan National High School, Tabaco City, Albay, Philippines wherein one class was randomly selected as the peer tutored group while the remaining four classes were considered the non-peer tutored groups. The peer tutoring sessions were conducted during the Independent/Cooperative Learning (ICL) period. The sources of data include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Through this method, it can be seen that students who act as tutors and students who were guided got selfimprovement (Berso & Lorente, 2020;Miquel & Duran, 2017). Several studies proved that the peer tutoring method improves student learning outcomes (Alegre et al, 2019;Berso & Lorente, 2020;Bulut, 2019;. The experimental class students had proven this by obtaining an average score higher than the control class.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Through this method, it can be seen that students who act as tutors and students who were guided got selfimprovement (Berso & Lorente, 2020;Miquel & Duran, 2017). Several studies proved that the peer tutoring method improves student learning outcomes (Alegre et al, 2019;Berso & Lorente, 2020;Bulut, 2019;. The experimental class students had proven this by obtaining an average score higher than the control class.…”
Section: Discussionmentioning
confidence: 98%
“…They are students who had participated in science competitions or who had a high score in the previous lesson to act as tutors. Through this method, it can be seen that students who act as tutors and students who were guided got selfimprovement (Berso & Lorente, 2020;Miquel & Duran, 2017). Several studies proved that the peer tutoring method improves student learning outcomes (Alegre et al, 2019;Berso & Lorente, 2020;Bulut, 2019;.…”
Section: Discussionmentioning
confidence: 99%
“…The study papers utilised were not subjected to any continent or country. Overall, the selected study papers were published from South Africa (e.g., Campbell, 2019), United States (Deshler et al, 2019), Australia (Johnston, 2021), China (Song et al, 2018), Indonesia (e.g., Baiduri, 2017), Pakistan (Nawaz & Rehman, 2017), Philippines (Berso & Lorente, 2020), Spain (e.g., Alegre et al, 2020), Taiwan (Chu et al, 2017), Turkey (Yaman, 2019) and United Kingdom (e.g., Zeneli et al, 2018). It was also found that the distribution of the studies by continent was mostly done in the Asian and European continents (Figure 3).…”
Section: Figure 2 Year Publication In the Reviewed Articles The Peer-...mentioning
confidence: 99%
“…A total of seventeen articles discussed the impact of the implementation of peer tutoring from the aspect of student academic achievement (e.g., Berso & Lorente, 2020). In general, most of the articles discussed the impact of academic achievement of tutors and tutees in implementing peer tutoring and the findings showed a positive impact of academic achievement as well as benefit through the program.…”
Section: Figure 5 Learning Outcomementioning
confidence: 99%
See 1 more Smart Citation